Time for new guidelines in advanced healthcare: the mission of The EPMA Journal to promote an integrative view in predictive, preventive and personalized medicine - Golubnitschaja, Olga (BioMed Central, 2012)
Changing long-held beliefs is never easy. As a consequence of the accumulating clinical data and knowledge about the epidemiology and pathological mechanisms of the most frequent causes of morbidity and mortality, we are currently reconsidering our view of the origins and progression of cardiovascular, oncologic and neurodegenerative diseases. Optimistic versus pessimistic prognosis for healthcare sector depends much on diagnostic, preventive and treatment approaches, which healthcare systems will preferably adopt in the near future. PPPM offers great promise for the future practice of medicine. We are pleased to announce this first open access volume of The EPMA Journal following its transfer to BioMed Central two years after publication of the first article in the journal.